Interpretative repertoires of the Venezuelan informal trader on the social network Twitter - Yalta Gonzales, Edgar Mauro (2022)
Venezuelan migration in Latin America is considered the most important migratory phenomenon in recent years and Peru has not been unaffected by this phenomenon. The Venezuelan community in Peru is often the victim of xenophobic and racist processes for reasons linked to informality and the use of public spaces. Rejection is frequently evidenced in the media, especially by users of social networks. This article aims to analyze, from the approach of Discursive Psychology, the interpretative repertoires that were constructed to discursively express the rejection by Peruvian users towards the Venezuelan informal trader in the social network Twitter. For this purpose, we selected a set of representative tweets that make explicit this rejection of Venezuelan informal traders. The results show the use of three main interpretative repertoires: invaders of public spaces, criminalization and nationalism-belonging.